2016
DOI: 10.18632/oncotarget.12514
|View full text |Cite
|
Sign up to set email alerts
|

p53 increase mitochondrial copy number via up-regulation of mitochondrial transcription factor A in colorectal cancer

Abstract: In colorectal cancer, no study has been carried out discovering the relationship among p53, mitochondrial transcription factor A (TFAM) expression and change of mitochondrial DNA (mtDNA) copy number. In our study, co-expression of p53 and TFAM was observed in colon adenocarcinoma tissues, paracancerous tissues and 9 colorectal cancer cell lines. Then, a significant linear correlation was established between either p53 or TFAM expression and advanced TNM stage, positive lymph nodes and low 5-year survival rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…P53 is involved in regulation of the cycle arrest, apoptosis and senescence . It not only interacts with the promotor of TFAM to activate TFAM transcription but also binds with TFAM to regulate cell death . However, whether TFAM can influence p53 has not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…P53 is involved in regulation of the cycle arrest, apoptosis and senescence . It not only interacts with the promotor of TFAM to activate TFAM transcription but also binds with TFAM to regulate cell death . However, whether TFAM can influence p53 has not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…TFAM is reported to be associated with tumorigenesis in breast, cervical, prostate, small cell lung cancers [12][13][14][15][16]. Also, frequent frameshift mutations in the coding mononucleotide repeat of TFAM was demonstrated in sporadic CRC derived cell lines and CRC tissues [17,18]. Previous study suggested that the reduced mtDNA copy number increased the sensitivity of tumor cells to chemotherapeutic drugs, suggesting that TFAM could be a potential contributor for tumor progression [19].…”
Section: Introductionmentioning
confidence: 99%
“…The tumour suppressor p53 plays an important role in many cellular processes, such as apoptosis, DNA repair, cell cycle arrest, angiogenesis or mitochondrial quality check . Mutations in the TP53 gene are frequently observed in CC cells, and most of them result in the loss of normal protein function .…”
Section: Discussionmentioning
confidence: 99%
“…p53 is a transcription factor that can regulate the expression of genes participating in mitochondrial quality control checks. For example, genes encoding TFAM or spermatogenesis associated 18 protein (SPATA18) were found to be the transcriptional targets for p53. Although TFAM functions as a mitochondrial transcription factor, which also plays an important role in mtDNA replication and repair, the SPATA18 mediates the repair or elimination of dysfunctional mitochondria in response to mitochondrial damage .…”
Section: Introductionmentioning
confidence: 99%